Couch Bookshelf Puncak Bumi Utama Sdn. Bhd. / Anis Nadia Anuar - Anuar, Anis Nadia (2019)
The summary from this case study need to focus on two major findings of the product which are non-friendly technology and lack of promotion in social media platforms. These two problem should be focused by the company to improve the product. For the first problem, the product should be implement new technologies to make the customer life easier while on the other hand for the second problem the company should using social media platforms for the product to attract more customers since nowadays majority of the people using their social media in daily basis.